The institutional underpinnings of the prospective euro adoption in Poland - Ryszard Rapacki (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper aims to assess both the explicit and implicit convergence criteria for Poland's possible membership in the Economic and Monetary Union, with special emphasis on institutional underpinnings of the country's prospects of adopting the euro. While the former set of criteria (embedded in the Maastricht Treaty) comprises fiscal and monetary indicators of nominal convergence, the latter highlight the resilience of a country to adverse asymmetric shocks and its ability to compete internationally, and point to the importance of labor mobility in particular and institutional quality in general as key shock-absorbing mechanisms and main drivers of a sustainable comparative advantage of a country. The paper focuses therefore on the evaluation of existing institutions and their evolution in Poland vis-à-vis the standards prevailing in the euro zone, as key determinants of the country's readiness to become an EMU member. The theoretical background of the assessment involved comprises two chief pillars: the optimum currency area theory (OCA) and the 'diversity of capitalism' (DoC) approach.
Conference: ICCEES IX World Congress, Makuhari, 3-8 August 2015; Additional information: Paper prepared for the ICCEES IX World Congress, Makuhari, 3-8 August 2015.
Keywords: E66; B52; 330; euro adoption; convergence; Euro; Convergence criteria